Disc Jockey jako twórca zależny – problem miksowania utworów w świetle przepisów ustawy z dnia 4 lutego 1994 r. o prawie autorskim i prawach pokrewnych - Piesiewicz, Piotr (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2003)
One of the fundamental issues regulated by the act on copyright law is the content of the rights vested in the author and related to his or her creation. The stipulations of the copyright law protect the author against an infringement of a personal bond relating him or her to the creation (personal copyrights) and provide him or her with economic benefits provided by the creation being exploited in various realms (copyright property law). The present paper addresses the problem of a disc jockey’s public presentation of music compositions and the protection of personal copyright and property law of the author of presented music.
Disc Jockey as a Dependent Artist - the Problem of Music Mixing in the Light of Regulations of the Act of February 4 th, 1994 on the Copyright Law and Related Laws